2009
DOI: 10.1007/s11663-008-9213-z
|View full text |Cite
|
Sign up to set email alerts
|

Subsolidus Phase Equilibria of Fe-Ni-X-O (X = Mg, Al) Systems in Air

Abstract: The phase equilibria of Fe-Ni-X-O (X = Mg, Al) systems, including their lower-order systems, at temperatures between 1200°C and 1600°C in air in the subsolidus region, have been experimentally studied. In the present study, the 'Fe 2 O 3 '-MgO, 'Fe 2 O 3 '-Al 2 O 3 , and NiO-Al 2 O 3 binary phase diagrams, as well as the ternary phase diagrams in the Fe-Ni-Mg-O and Fe-Ni-Al-O systems projected onto the Fe-Mg-Ni and Fe-Al-Ni planes, have been constructed. Differences have been found between the present measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 27 publications
(55 reference statements)
2
16
0
Order By: Relevance
“…However, none of the ternary oxides showed to dissolve any significant concentrations of ZnO and the compositions could therefore be regarded as very close to the Fe 2 O 3 -Al 2 O 3 section. Hansson et al [40] also used EPMA for their phase composition determinations and notably concluded similar discrepancies compared to previous data as Rhamdhani et al [37] would do some years later.…”
Section: The Al-fe-o System In the Literaturesupporting
confidence: 56%
See 3 more Smart Citations
“…However, none of the ternary oxides showed to dissolve any significant concentrations of ZnO and the compositions could therefore be regarded as very close to the Fe 2 O 3 -Al 2 O 3 section. Hansson et al [40] also used EPMA for their phase composition determinations and notably concluded similar discrepancies compared to previous data as Rhamdhani et al [37] would do some years later.…”
Section: The Al-fe-o System In the Literaturesupporting
confidence: 56%
“…The tetrahedral sites and the regular octahedral sites have preference for Al whereas Fe prefers the two irregular six-fold sites. Although non-stoichiometric compositions have been observed [36,37], it is modeled as a stoichiometric compound in the current work for the sake of simplicity. Its Gibbs energy function is hence given by…”
Section: Tablementioning
confidence: 99%
See 2 more Smart Citations
“…16,17) For the commercial PM 2000 steel, detailed processing procedures are not available. It has been reported that the Al2Fe2O6 phase formed at a temperature of about 1 318-1 410°C 18) and 1 300-1 400°C, 19) whereas the Al3Ti5O2 phase formed at a relative low temperature of 900°C. 20) High pressure and severe plastic deformation during hot isostatic pressing and hot-rolling processes accelerated probably the formation of the Al2Fe2O6 phase, i.e., it formed at lower temperature.…”
Section: Aluminum Oxide Phasementioning
confidence: 99%